2022
DOI: 10.1002/adfm.202201127
|View full text |Cite
|
Sign up to set email alerts
|

Structural Buffer Engineering on Metal Oxide for Long‐Term Stable Seawater Splitting

Abstract: Seawater electrolysis is an attractive technique for massive green hydrogen production owing to the dominant advantages of seawater resources, namely low‐cost and limitlessness. However, the oxygen evolution reaction (OER) catalysts will be easily deactivated for severe seawater Cl− permeation and corrosion. Herein, a structural buffer engineering strategy is reported to endow the Co2(OH)3Cl with long‐term operation stability and a high OER selectivity of ≈99.6% in seawater splitting. The lattice Cl− of Co2(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 35 publications
0
64
0
Order By: Relevance
“…For example, Zhuang et al reported a structural buffer strategy to effectively avoid the negative effect of chloride ions invasion and boost OER activity (Figure 11A), which could be demonstrated by the comparison of Co 2 (OH) 3 Cl and Co(OH) 2 (Figure 11B, C). 66 Typically, DFT study further verified the crucial role in corrosion resistance and performance enhancement capability of the lattice Cl À species, which was based on the two CER reaction pathways. In addition, intermediate (Cl à ) on the site of O-Co-Cl with stronger adsorption strength proved that O-Co-Cl sites tend to be preferential CER reaction sites (Figure 11D-H).…”
Section: Transition Metal Oxides and (Oxy) Hydroxidementioning
confidence: 75%
See 2 more Smart Citations
“…For example, Zhuang et al reported a structural buffer strategy to effectively avoid the negative effect of chloride ions invasion and boost OER activity (Figure 11A), which could be demonstrated by the comparison of Co 2 (OH) 3 Cl and Co(OH) 2 (Figure 11B, C). 66 Typically, DFT study further verified the crucial role in corrosion resistance and performance enhancement capability of the lattice Cl À species, which was based on the two CER reaction pathways. In addition, intermediate (Cl à ) on the site of O-Co-Cl with stronger adsorption strength proved that O-Co-Cl sites tend to be preferential CER reaction sites (Figure 11D-H).…”
Section: Transition Metal Oxides and (Oxy) Hydroxidementioning
confidence: 75%
“…To combat serious environmental pollution and energy crisis, renewable clean energy H 2 has attracted wide attention, and seawater with abundant reserves is Reproduced with permission from reference [66]. Copyright 2022, Wiley-VCH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the vacancy formed by the continuous leaching of Cl − of Co 2 (OH) 3 Cl in the OER process, which could become the preferred attack site of Cl − in seawater to avoid the structural collapse of the catalyst. 22 Fe-Ni(oxy)hydroxide is the most important active species in the Adsorbate Evolution Mechanism (AEM). 23,24 But now the research difficulty of Fe-Ni(oxy)hydroxide is how to prepare it quickly, modify its catalytic surfaces accurately, and maintain its catalytic activity for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the vacancy formed by the continuous leaching of Cl − of Co 2 (OH) 3 Cl in the OER process, which could become the preferred attack site of Cl − in seawater to avoid the structural collapse of the catalyst. 22…”
Section: Introductionmentioning
confidence: 99%